1998
DOI: 10.1076/jcen.20.3.376.819
|View full text |Cite
|
Sign up to set email alerts
|

Acquisition and Storage Deficits in Multiple Sclerosis

Abstract: This study examined whether verbal and visual memory impairments in multiple sclerosis (MS) are attributable to deficits in acquisition, storage, or retrieval. Volunteers with MS (n = 40) and healthy controls (n = 20) rehearsed a word list and a checkerboard pattern using a selective reminding procedure until two consecutive error-free trials were attained. Recall and recognition were assessed after 30 min and 90 min (and 1 week for verbal material) delays. The MS group required significantly more trials to at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

15
116
0
8

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 179 publications
(139 citation statements)
references
References 0 publications
15
116
0
8
Order By: Relevance
“…Many studies support the notion that reduced verbal memory functioning in MS is associated with reduced processing speed (Arnett, 2004;DeLuca et al, 1994;Litvan et al, 1988), although a few do not (DeLuca et al, 1998;Thornton & Raz, 1997). One study that did not find significant correlations between verbal memory and processing speed used a processing speed variable that likely had reduced sensitivity because it was adjusted to keep initial performance constant (DeLuca et al, 1998), while another study with a similar finding used an index that does not adequately assess processing speed (Thornton & Raz, 1997). Other studies have reported the more general finding that MS patients have impaired information processing speed (Archibald & Fisk, 2000;DeLuca, Chelune, Tulsky, Lengenfelder, & Chiaravolloti, 2004;Demaree, DeLuca, Gaudino, & Diamond, 1999;Litvan et al, 1988).…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Many studies support the notion that reduced verbal memory functioning in MS is associated with reduced processing speed (Arnett, 2004;DeLuca et al, 1994;Litvan et al, 1988), although a few do not (DeLuca et al, 1998;Thornton & Raz, 1997). One study that did not find significant correlations between verbal memory and processing speed used a processing speed variable that likely had reduced sensitivity because it was adjusted to keep initial performance constant (DeLuca et al, 1998), while another study with a similar finding used an index that does not adequately assess processing speed (Thornton & Raz, 1997). Other studies have reported the more general finding that MS patients have impaired information processing speed (Archibald & Fisk, 2000;DeLuca, Chelune, Tulsky, Lengenfelder, & Chiaravolloti, 2004;Demaree, DeLuca, Gaudino, & Diamond, 1999;Litvan et al, 1988).…”
Section: Discussionmentioning
confidence: 93%
“…The primary pathological process in MS involves demyelination seen as hyperintensities on T2 or FLAIR magnetic resonance imaging (MRI), and in theory leads to disruption of corticalsubcortical circuits (Filley, 1998(Filley, , 2012Mesulam, 1990). Many studies support the notion that reduced verbal memory functioning in MS is associated with reduced processing speed (Arnett, 2004;DeLuca et al, 1994;Litvan et al, 1988), although a few do not (DeLuca et al, 1998;Thornton & Raz, 1997). One study that did not find significant correlations between verbal memory and processing speed used a processing speed variable that likely had reduced sensitivity because it was adjusted to keep initial performance constant (DeLuca et al, 1998), while another study with a similar finding used an index that does not adequately assess processing speed (Thornton & Raz, 1997).…”
Section: Discussionmentioning
confidence: 96%
“…A wide symptom array follows, including cognitive impairment [2]. Learning and memory is the most common cognitive symptom [2,3], evident in 40-65% of patients [4] and demonstrated to be a result of new learning deficits [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…Further, the Relative Consequence Model proposed by DeLuca and colleagues [5] suggests that the processing speed deficit observed in individuals with MS is primary, and in turn, is the source of the deficits in other cognitive domains. This has received support in the literature [7,[12][13][14]. Pathological explanations for the processing speed deficits have been postulated [15][16][17]; however, Hillary [18] suggests that reaction time has been understudied.…”
Section: Introductionmentioning
confidence: 89%